Perancangan Sistem Informasi Pemesanan Interior pada PT. Cipta Kreasi Buana Berbasis Web Menggunakan Metode Prototype - Ratna Sari Dewi (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2023)
Various information technologies are utilized for work purposes, one of which is web-based applications. PT. Cipta Kreasi Buana is a company engaged in interior design and furniture since 2015. In its business processes, the company often encounters difficulties in managing the ordering process for interior products. The existing manual system results in recording errors, inefficient scheduling, and a lack of transparency for customers due to insufficient visibility regarding the status of their orders. Additionally, the company recognizes the importance of keeping up with technological trends and digitalization in business to remain competitive and tap into new digital markets online. To address these issues, the researcher designed a web-based interior sales information system using a prototype method. This approach encompasses stages such as user needs analysis, interface and database structure design, prototype development, testing, and iteration. The research outcome includes the design of a website to tackle existing problems. Consequently, the generated system operates effectively, improving efficiency and accuracy in the ordering process for interior products. This has a positive impact on customers and enhances the company's sales.